147 Siponimod preserves retinal thickness: findings from the EXPAND OCT substudy. Issue 9 (12th August 2022) - Vermesch, Patrick; Gold, Ralf; Bar-Or, Amit; Cree, Bruce; Fox, Robert; Giovannoni, Gavin; Li, Bingbing; Piani-Meier, Daniela; Karlsson, Goeril; Kappos, Ludwig
Abstract : Aim: To evaluate changes in retinal thickness (µm), including the retinal nerve fibre layer (RNFL) and combined ganglion cell and inner plexiform layers (GCIPL), in patients receiving siponimod or placebo. Methods: Changes in optical coherence tomography (OCT) measurements from screening to M12 and M24 were compared between the two treatment groups using mixed models for repeated measures adjusted for treatment, age, sex and respective baseline OCT variables. Results: The OCT sub-study included 159 patients (siponimod, n=104; placebo, n=55). RNFL thickness at M12 numerically favoured siponimod (0.39 vs −0.99; p=0.099) but not at M24 (−0.05 vs. 0.48; p=0.642). However, fewer assessments were available for RNFL at M24 than M12. The between-group difference in GCIPL thinning was 0.21 (−2.55 vs −2.76; p=0.875) at M12 and 3.82 (−0.47 vs −4.29; p=0.01) at M24. Siponimod reduced retinal thinning vs placebo at M12 (change from baseline: 0.66 vs −1.86; p=0.006) and M24 (−0.05 vs −2.3; p=0.033). Changes of retinal thickness and GCIPL at the subfield areas also favoured siponimod over placebo. Conclusions: These results support the sensitivity of OCT as a measure of tissue damage in progressive MS and are in line with previously reported beneficial effects of siponimod on other neurodegeneration related outcomes. Funding: Novartis Pharma AG, Basel, Switzerland.